IDENTIFICATION OF COMPLEX VOLATILE ORGANIC COMPOUNDS IN MUNICIPAL LANDFILL LEACHATE BY HEAD-SPACE SOLID PHASE MICROEXTRACTION AND GCXGC-qMS ANALYSIS - BELDEAN-GALEA, Mihail Simion; THÉBAUT, Didier; VIAL, Jérôme; COMAN, Virginia (Studia Universitatis Babeș-Bolyai Chemia, 2017)
A method for the identification of different classes of volatile organic compounds in the municipal landfill leachate using solid phase microextraction and comprehensive two dimensional gas chromatography coupled with mass spectrometry (SPME-GCxGC-qMS) is elaborated. The results showed that the proposed protocol is able to separate and identify in a single run different classes of volatile organic compounds responsible for the odor of leachate such as carbonyl compounds, aromatic compounds, terpenes, phenolic compounds and nitrogen and sulfur containing compounds. The use of solid phase microextraction not only eliminate the solvent from the samples processing step but also considerably reduces the time and the volume of the sample necessary for this step, being a viable green alternative for this type of analysis. The use of mass spectrometry gives the possibility to indentify many other compounds responsible for municipal landfill leachate odor, creating the premises for a better assessment of chemical composition of leachate. The developed protocol shows good performances in term of repeatability, linearity, limit of detection and limit of quantification being applicable for the real municipal landfill leachate analysis.